Assessment of fracture toughness in fibrous concrete via Brazilian test: Experimental study with low-clinker cementitious binder - Venu H.; Murali G.; Ramkumar V.R.; Sieh Kiong T.; Mazlini Razali N. (Elsevier B.V., 2025)
As the predominant and cost-effective material in the construction industry, concrete is susceptible to tension weaknesses, leading to significant flaws such as cracking and brittle fracturing. Recent advancements in fibrous concrete have emerged as a solution to mitigate these issues. Incorporating steel fibers in concrete has emerged as a promising solution to improve crack resistance and structural integrity. This study focuses on developing eco-friendly concrete using a low-clinker cementitious binder and short steel fibers to enhance fracture toughness and mitigate the environmental impact by effectively utilizing lime sludge. Concrete specimens were prepared with three binder types: treated lime sludge (TLS) at 15 % and 30 % and calcined clay (CC) at 15 % and 30 %, replacing conventional clinker. Short steel fibers were added at 1.5 % by volume to enhance mechanical properties. Fracture toughness was evaluated using notched Brazilian disc specimens, assessing mode I, II, and mixed-mode (I/II) fracture at multiple notch orientations (? = 0, 15, 28.83, 45, 60, 75, and 90). Microstructural analysis during strength development was performed using scanning electron microscopy and X-ray diffraction. The findings revealed that specimens containing 15 % TLS, 30 % CC, and 1.5 % steel fibers exhibited the highest fracture toughness. Mode II fracture toughness exceeded mode I, indicating improved resistance to crack propagation. The addition of fibers to the specimens under mode II demonstrated improved fracture toughness, ranging from 0.44 to 0.53 MPam^1/2 compared to the corresponding non-fibrous specimens. The fibrous specimens showed significantly higher ultimate loads at ? = 90 compared to ? = 0, indicating superior crack resistance and structural integrity under perpendicular loading conditions. The Brazilian disc specimens demonstrated variability in fracture toughness across different loading orientations, highlighting their suitability for mixed-mode fracture assessment. ? 2024 Elsevier Ltd